The Band Structure of a Rare Earth Element of Promethium (III) Oxide (Pm2O3) Calculated Using Density Functional Theory - Mohd Rafi N.A.; Ahmad Nazrul Rosli (Institute of Physics Publishing, 2024)
Indexed by Scopus